PENILAIAN KESEHATAN KEBUN BENIH SEMAI Pinus merkusii DENGAN METODE FHM (FOREST HEALTH MONITORING) DI KPH SUMEDANG Health Assessment for Seedling Seed Orchard of Pinus merkusii Using FHM (Forest Health Monitoring) Method in KPH Sumedang - Supriyanto .; Taufik Iskandar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Pine (Pinus merkusii) is tree species that provides timber and gum rosin. To meet the needs of wood and non wood (gum rosin) products, planting by using superior or high quality seeds are needed. Seed procurements for planting are obtained from seedling seed orchard (SSO). However, Cijambu’s SSO was attacked by pine woolly aphid (Pineus boerneri). Therefore, assessment of Cijambu’s SSO needs to be done to evaluate the severity pest attacks that could affect to the quality and the quantity of seed production. Forest Health Monitoring (FHM) method is one of the methods to assess the health level of a stand. The number of trees found in all cluster plots in Cijambu’s SSO were 270 trees. Based on the value of the VCR (Visual Crown Rating), the trees located in all cluster plot have health level between low to high. Based on the value of the VCR showed 38.52% (104 trees) having VCR’s value was high, 49.26% (133 trees) having VCR’s value was middle; 12.22% (33 trees) having VCR’s value was low; and no tree having very low VCR’s value. The average of VCR’s value in all cluster plots were 3.25 and classified as middle health. Based on the value of TDLI (Tree Damage Level Index) from 270 trees in all cluster plot showed that 189 trees (70.00%) in healthy condition; 69 trees (25.56%) in slight damage condition; 11 trees (4.07%) in middle damage condition; and 1 tree (0.37%) in heavy damage condition. The value of damage in all cluster plots (ALI) was 261.22 and classified as in health condition. The trees located in all cluster plots were mostly suitable to be seed sources as 242 trees (89.63%), while 28 trees (10.37%) were not suitable for seed sources.Keywords: Forest Health Monitoring, Pinus merkusii, seedling seed orchard, Tree Damage Level Index, Visual Crown Rating